A Resource-Based Perspective to Assess Firms’ Profitability in the Food Industry: Evidence from the Italian Cheese Industry - Eugenio D’Angelo (European Scientific Journal, ESJ, 2018)
The purpose of this paper is to investigate the determinants of firms’ competitive advantage and performance in the Italian food industry, with specific reference to the cheese sector. This aim is consistent with the 3-year research program outlined by the agreement between the Pegaso Telematic University and the Gerardi & Fortura Limited Liability Company, subscribed in November 2015 (02/24/2015) and assigned to the author. The paper investigates the source of superior performance in the Italian cheese industry using the well-known Resource Based Theory. The empirical analysis is conducted on a sample of 110 firms and over a 10-year period of observation. An OLS regression is used to evaluate the impact of a bundle of resources on firms’ performance. Findings show that physical and financial resources have the major effect on firms’ return on assets, whereas intangible assets, capabilities and human resources have a lower and ambiguous effect.